PERANAN MAIA KULIAH AUDITING DALAM MENGURANG] EXPEGTATION GAP - Maylia Pramono Sari (Jurnal Riset Akuntansi dan Keuangan, 2008)
Expectation Gap is the dffirent between what is believed by commwtity and the finoncial stetemeftt uyer as atditor'responsibility with what is believed by ruditor as theirb responsibility (AICPA, 1991). Expectation Gap between aaditor and comwunity and financial statement user is oce$r ift Indbnesia, so this subject in university'degreecan reduce the dffirences. Based on problem description in this research, the goal of this research is to prove the dffirence abaut perception of auditor's role ond responsibility. And the otlwr goal is to find the speeific pnocess of auditing which has dane hy the s*dmt in the beginning of subjeet and at thc end of the sublect of auditing. The result of the reseach shows that perception abaut auditorb role and responsibilities, incltde process of the auditing. The accounting student, who has not jointed the subject is signifcanlly dffirent with the peirception og accountngstudent who has jointed the subject. Hypothesis test is using Wilcoxon Rank Test. In the Wilcoxon Rank Test which the probability < 0,05, so HI accepted.Keywords: Expectation Gap; Atditorb Rale and Responsibility; Audit Process